Respuesta :
Answer:
y = - 49
Step-by-step explanation:
The vertex lies on the axis of symmetry which is at the midpoint of the zeros.
To find the zeros, let f(x) = 0, that is
(x - 3)(x + 11) = 0
Equate each factor to zero and solve for x
x - 3 = 0 ⇒ x = 3
x + 11 = 0 ⇒ x = - 11
[tex]x_{vertex}[/tex] = [tex]\frac{-11+3}{2}[/tex] = [tex]\frac{-8}{2}[/tex] = - 4
To find the y- coordinate of the vertex evaluate f(- 4)
f(- 4) = (- 4 - 3)(- 4+ 11) = (- 7)(7) = - 49
Answer:
Step-by-step explanation:
hello :
f(x)=-(x-3)(x+11) = -(x²+11x-3x-33)
f(x) = -x²-8x+33 = -(x²+8x-33)
f(x) = - (x²+8x+16-16-33)=-(x²+8x+16) + 49
f(x) = - (x+4)²+49 .... vertex form
the y-value of the vertex of the function is 49 when x= - 4